An investigation of gaseous hydrogen storage characterizations of Mg–Y–Ni–Cu alloys synthesized by melt spinning. Issue 51 (14th August 2018) - Zhang, Yanghuan; Ji, Yanquan; Yuan, Zeming; Bu, Wengang; Qi, Yan; Guo, Shihai
Abstract : Melt spinning enables the crystalline alloy to be strongly disordered and nanostructured, thus enhancing the hydrogen storage kinetics of Mg25− x Y x Ni9 Cu. Abstract : Melt spinning was successfully utilized to prepare Mg25− x Y x Ni9 Cu ( x = 0, 1, 3, 5, 7) alloys, producing nanocrystalline and amorphous structures with improved hydrogenation and dehydrogenation performances. The influence of spinning rate on hydrogenation and dehydrogenation thermodynamics and kinetics was studied in detail. XRD and TEM were utilized to characterize the alloy structures. Hydrogenation and dehydrogenation performances were investigated by Sievert apparatus, DSC and TGA connected to a H2 detector. Dehydrogenation activation energies were estimated using both Arrhenius and Kissinger methods. Results show that melt spinning significantly decreases thermodynamic parameters (Δ H and Δ S ) and ameliorates desorption kinetics. Dehydrogenation activation energy markedly lowers with increase in spinning rate and is the real driver of amelioration of dehydrogenation kinetics caused by increasing Y content.